Preparation, physicochemical and biological evaluation of quercetin based chitosan-gelatin film for food packaging. (1st January 2020) - Yadav, Srasti; Mehrotra, G.K.; Bhartiya, Prabha; Singh, Anu; Dutta, P.K.
Highlights: Physicochemical and Mechanical properties of chitosan-gelatin based films containing Quercetin-starch (Q) were investigated. Quercetin-starch improved antioxidant property as well as antibacterial property. Ch-ge-Q films protected foods from UV radiation. Quercetin-starch improved mechanical properties of the film as well as WVP. Abstract: Ecofriendly chitosan-gelatin (Ch-ge) bio-composite films containing Quercetin-starch (Q) were synthesized using solution casting method. Physicochemical characteristics and mechanical properties of the resulting chitosan-gelatin containing Quercetin-starch films (Ch-ge-Q) were studied using UV, FTIR, XRD and SEM techniques. The films were also investigated for their swelling, water-vapor permeability (WVP), water solubility properties. The FTIR spectra confirmed the chemical interactions between the chitosan-gelatin and Q. Surface morphology of prepared film was analyzed by the SEM imaging while XRD spectra suggest the expanded crystallinity of the film with the addition of Q. The film also showed enhanced barrier property against UV rays. The reduction of water-vapor permeability and increase in tensile strength while a decrease in elongation at break has been observed in the Ch-ge-Q film compared to Ch-ge film. The antibacterial activity of Ch-ge-Q film against both gram positive ( B. substilis ) and gram negative ( E. coli ) bacteria suggested the Q loaded Ch-ge films as more feasible antibacterial candidate especially against the strain E. coli . The antioxidant activity of the Ch-ge-Q film was evaluated using the DPPH and ABTS as standards and corresponded to 81.45% of DPPH and 72.2% of ABTS scavenging activities. It was observed that the film containing Quercetin-starch presented superior antioxidant activity results in comparison to Ch-ge film promising its application in food packaging.